2016
DOI: 10.5089/9781475519983.001
|View full text |Cite
|
Sign up to set email alerts
|

Middle East and Central Asia: A Survey of Gender Budgeting Efforts

Abstract: Gender budgeting uses fiscal policies to promote gender equality and women's advancement, but is struggling to take hold in the Middle East and Central Asia. We provide an overview of two gender budgeting efforts in the region-Morocco and Afghanistan. Achievements in these two countries include increasing female primary and secondary education enrollment rates and reducing maternal mortality. But the region not only needs to use fiscal policies for women's advancement, but also reform tax and financial laws, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…More recently, Downes et al (2017) found that making civic audits and open data resources available to nongovernmental organizations has been helpful in supporting the growth and implementation of gender equity policies in OECD countries. Kolovich and Shibuya (2018) found the same to be true in India.…”
Section: Support Of Organizations Outside Governmentmentioning
confidence: 67%
See 1 more Smart Citation
“…More recently, Downes et al (2017) found that making civic audits and open data resources available to nongovernmental organizations has been helpful in supporting the growth and implementation of gender equity policies in OECD countries. Kolovich and Shibuya (2018) found the same to be true in India.…”
Section: Support Of Organizations Outside Governmentmentioning
confidence: 67%
“…More recently, Downes et al (2017) found that making civic audits and open data resources available to nongovernmental organizations has been helpful in supporting the growth and implementation of gender equity policies in OECD countries. Kolovich and Shibuya (2018) found the same to be true in India. And, in countries across the world, “[t]he role of UN Women (formerly UNIFEM) has been critical in initiating gender budgeting efforts … and helping sustain them” (Stotsky, 2016, p. 19).…”
Section: Enabling Factors For Grb Successmentioning
confidence: 69%
“…However, the degree of implementation of gender budgeting varies widely across countries and governmental levels (Budlender, 2002;Downes et al, 2016;Fragoso & Enríquez, 2016;IMF, 2017;Kolovich & Shibuya, 2016;Stotsky, 2016), and there often exist shortcomings in the systematic collection and analysis of sex-disaggregated data, which is considered a crucial prerequisite for successful gender budgeting initiatives (Budlender & Hewitt, 2003;Elson, 2002b). One of the most active international organizations in the field of international development, economics and finance, the IMF, has conducted several surveys of gender budgeting efforts in different world regionsin Asia (Chakraborty, 2016), Europe (Quinn, 2016), the Middle East and Central Asia (Kolovich & Shibuya, 2016), and Sub-Saharan Africa (Stotsky et al, 2016), as well as in the Western Hemisphere more generally (Fragoso & Enríquez, 2016). The latter adds a more balanced view of international developments in gender budgeting given that prior work has mainly focused on developing countries that have usually been placed outside the traditional concept of the Western Hemisphere (see Holvoet, 2007).…”
Section: Gender Budgetingan Overviewmentioning
confidence: 99%
“…Source: IMF (2017a) (Kolovich and Shibuya, 2016).  Uganda introduced a Gender and Equity Compliance Certificate into their Public Finance Management Act in 2015.…”
Section: Stages Of the Budget Processmentioning
confidence: 99%